GABAA Receptor-Mediated Epileptogenicity in Focal Cortical Dysplasia (FCD) Depends on Age at Epilepsy Onset - Banerjee, Jyotirmoy; Dey, Soumil; Dixit, Aparna Banerjee; Doddamani, Ramesh; Sharma, Meher Chand; Garg, Ajay; Chandra, P. Sarat; Tripathi, Manjari (Frontiers in Cellular Neuroscience, 2020)
Enhanced spontaneous GABAA receptor activity is associated with focal cortical dysplasia (FCD), a developmental malformation of the cerebral cortex. Clinical manifestations in FCD vary with age at epilepsy onset with a more favorable prognosis in patients with late onset (LO) compared to that in cases with early onset (EO). This study was designed to test the hypothesis in FCD that spontaneous GABAA receptor-mediated epileptogenicity depends on the age at epilepsy onset and varies between patients with early and late onset age in FCD. To this end brain specimens were obtained from the maximal spiking region (MAX) and minimal spiking region (MIN) of the epileptic foci of EO (n = 14, mean age = 10.6 ± 2.9 years) and LO (n= 10, mean age = 27 ± 5.6 years) patients undergoing electrocorticography (ECoG) guided surgery. Whole-cell patch clamp technique was used to record spontaneous GABAergic currents from normal-looking pyramidal neurons in slice preparations of resected brain samples. We detected higher frequency and amplitude of GABAergic events in MAX samples compared to MIN samples of LO patients, while they were comparable in MIN and MAX samples of EO patients. Further GABAergic activity in the MIN and MAX samples of EO patients was higher than the MIN samples of LO patients. This suggests that in LO patients, GABAA receptor-mediated epileptogenicity is confined only to the high spiking areas, but in EO patients, it affects low spiking regions as well.